Efeito do uso tópico do extrato etanólico de folhas de Maytenus ilicifolia no reparo de feridas cutâneas - Moura, Francyelle Borges Rosa de (2017)
Maytenus ilicifolia, commonly known as espinheira-santa (ES), is widely usedas analgesic, antiseptic, curative, anti-inflammatory and antiulcerogenic, being the last one the most highlighted characteristic by scientific studies. The current analysis evaluated the effect of topical use of the ethanol extract from the leaves of ES in the repair of cutaneous wounds, after 3 and 7 days, being approved by the Ethics Committee (062/2016) of the Federal University of Uberlandia. Four wounds were performed in back of 64 BALB/c mice, being further treated with vaseline/lanolin in the control group and an ointment with 2% (ES 2%), 4% (ES 4%) and 6% (ES6%).Morphological and biochemical evaluations were performed to verify the evolution of the closure and a resolution of the inflammatory process. The results were used as standard error, ANOVA, two-way and Bonferroni post-test, with p <0.05. All concentrations improved or wound closure except ES 2% on the fifth day. In 3 days of treatment, an increase in the number of mast cells in ES 4% and ES 6% and reduction in neutrophil activity. Macrophages activity was reduced in ES 2% and ES 4%. Hemoglobin, total collagen and soluble collagen increased in ES 4%. Pro-MMP2 and MMP2 were observed only on 3-day wounds. Pro-MMP9 and MMP9 were increased in ES4% and ES6% with 3 days of treatment. On the seventh day, there was an increase in the number of mast cells in ES 6%, increase on the activity of neutrophils in all treatments and macrophage activity increased in ES 4%. In this period, it was also observed a reduction in the hemoglobin dosage in ES 4% and ES 6%. At 7 days, the soluble collagen was higher in the ES 4% group. There was no difference in type I and III collagen in 3 and 7 days. In conclusion, the ointment containing 4% of M. ilici- folia can be considered more effective, being able to optimize the repair in cutaneous wounds. This concentration had an anti-inflammatory effect (reduced neutrophil and macrophage activity), and increased collagen deposition and pro-MMP9 and MMP9. Collagen increase reinforces the matrix resistance, besides promoting a migration and proliferation of cells essential for a wound healing, which also count on with the participation of MMPs